2015
DOI: 10.1371/journal.pone.0118506
|View full text |Cite
|
Sign up to set email alerts
|

Natural Indoles, Indole-3-Carbinol (I3C) and 3,3’-Diindolylmethane (DIM), Attenuate Staphylococcal Enterotoxin B-Mediated Liver Injury by Downregulating miR-31 Expression and Promoting Caspase-2-Mediated Apoptosis

Abstract: Staphylococcal enterotoxin B (SEB) is a potent superantigen capable of inducing inflammation characterized by robust immune cell activation and proinflammatory cytokine release. Exposure to SEB can result in food poisoning as well as fatal conditions such as toxic shock syndrome. In the current study, we investigated the effect of natural indoles including indole-3-carbinol (I3C) and 3,3’-diindolylmethane (DIM) on SEB-mediated liver injury. Injection of SEB into D-galactosamine-sensitized female C57BL/6 mice r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…Draining lymph node cells from DTH mice were transfected (HiPerFect- Qiagen) with either miRNA mimics or inhibitors (Qiagen) for 6 h with target gene expression assessed 24 h after transfection. The transfection was performed as detailed in our previous publications [11, 40]. We found that miR-29b inhibitor significantly increased IFN-γ levels compared to miR-29b overexpression (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Draining lymph node cells from DTH mice were transfected (HiPerFect- Qiagen) with either miRNA mimics or inhibitors (Qiagen) for 6 h with target gene expression assessed 24 h after transfection. The transfection was performed as detailed in our previous publications [11, 40]. We found that miR-29b inhibitor significantly increased IFN-γ levels compared to miR-29b overexpression (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Transfection was performed as described (Busbee et al, 2015). Splenocytes were cultured in complete (10% FBS, 10 mM L-glutamine, 10 mM Hepes, 50 mM b-mercaptoethanol, and 100 mg/ml penicillin) RPMI 1640 medium (11875-093; Life Technologies Corp., Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, a number of non‐protein molecules (hormones and indoles) were demonstrated to regulate miR‐31 expression (Kuokkanen et al, ; Busbee et al, ). A number of studies reported that miR‐31 expression is activated by RELA (p65 subunit of NF‐κB) and SP1 (a zinc‐finger transcription factor) in esophageal cells under conditions that lack zinc (Alder et al, ; Fong et al, ; Taccioli et al, ).…”
Section: Regulation Of Mir‐31 Expressionmentioning
confidence: 99%